2014
DOI: 10.1186/1471-2172-15-22
|View full text |Cite
|
Sign up to set email alerts
|

The strength of the antibody response to the nematode Ascaris lumbricoides inversely correlates with levels of B-Cell Activating Factor (BAFF)

Abstract: BackgroundB-Cell Activating Factor (BAFF) is a cytokine regulating antibody production. Polymorphisms in the gene encoding BAFF were associated with the antibody response to Ascaris but not to mite allergens. In the present study we evaluated the relationship between BAFF and specific antibodies against Ascaris and mites in 448 controls and 448 asthmatics. Soluble BAFF was measured by ELISA and BAFF mRNA by qPCR. Surface expression of BAFF and its receptor (BAFF-R) was analyzed by flow cytometry.ResultsIndivid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 59 publications
(74 reference statements)
0
14
0
Order By: Relevance
“… a Asthmatic patients are a representative group for analyzing IgE response to Ascaris since it has been described that asthmatics have a higher antibody response to nematodes [1, 20]. …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“… a Asthmatic patients are a representative group for analyzing IgE response to Ascaris since it has been described that asthmatics have a higher antibody response to nematodes [1, 20]. …”
Section: Methodsmentioning
confidence: 99%
“…The genetic background of this population resulted from racial admixture between Native Americans, Spaniards, and an important proportion (37.9%) of African ancestry [27, 28]. The DNA samples (from peripheral blood) were obtained from a well-characterized repository at the Institute for Immunological Research in Cartagena, Colombia; they were extracted between 2002 and 2004 and have been kept at -80°C [1, 20]. Each DNA sample used for sequencing was evaluated for DNA integrity by visualization in 1% agarose gel and had A 260 /A 280 ratio between 1.8 and 2.09 (mean, sd, 1.93±0.05).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…BAFF is a member of the tumor necrosis factor (TNF) families and plays an important role in regulation of B cell survival, proliferation, differentiation, maturation, and immunoglobulin production. It is expressed by innate immune cells such as macrophages/monocytes, DCs, and activated T cells and also by nonlymphoid cells like epithelial cells [56, 57]. Recently, Shen et al [58] revealed that BAFF could promote the survival/proliferation of mouse splenic B cells.…”
Section: The Effect Of Baff On Tlr4-mediated B Cell Activationmentioning
confidence: 99%